Development of seblak cracker MSMEs in increasing innovation - Siti Nabila, Ivo; Febrianti, Anggreani; L.P Ramli, Rimayang Anggun; Yona, Mira (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Economy is one of the main pillars that supports human life and society as a whole. In every country, the economy is an important determinant of growth and development, both through the production of goods and services, consumption, investment, and government policies. Micro, Small, and Medium Enterprises (MSMEs) are one of the important players in the economy, both at the local and national levels, KSungai Binti Old Village Rw.12 is an old village where the Latansa Cracker Factory is produced with the aim of helping to increase the market reach of Latansa cracker business owners. This research activity was carried out through UMKM development activities by providing innovation in the form of making new products from processed crackers to add new variations to cracker products that have been marketed previously. This activity was carried out using an experimental approach, where this activity produced new products from processed raw crackers into dry seblak cracker snacks, this activity is expected to help develop the business of UMKM owners, increase market reach with marketing strategies, increase market competitiveness, and this new product is also expected to be able to provide added value to their business.